2012
DOI: 10.1521/aeap.2012.24.5.469
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of Condom Use Among Chinese College Students in Hunan Province

Abstract: A cross-sectional survey was conducted to test an integrated model of condom use with a sample of 490 sexually active Chinese college students. A number of variables in the integrated model were predictors of condom use, explaining 33.4% of the variance in use. Partner communication was the strongest predictors (β = .317, SE = .038, p < .001). Self-efficacy (β = .252, SE = .076, p < .001), positive attitudes (β = .150, SE = .060, p < .001), and social norms (β = .207, SE = .080, p < .001) were also significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 48 publications
(47 reference statements)
2
10
0
Order By: Relevance
“…This finding is in line with previous studies of education programs that promoted cervical cancer prevention behaviors and HIV prevention and were effective in increasing participants' self-efficacy for related behaviors (Kaponda et al, 2011). Moreover, previous studies reported that college students' self-efficacy for condom use was a strong predictive factor for the intent to use condoms (Lee, 2010;Xiao, 2012). However, even after intervention, participants' confidence about communication with their partners about safer sex and condom negotiation strategies (e.g., refusal of sex without a condom) in this study was relative lower than other abilities to successfully practice cervical cancer prevention behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…This finding is in line with previous studies of education programs that promoted cervical cancer prevention behaviors and HIV prevention and were effective in increasing participants' self-efficacy for related behaviors (Kaponda et al, 2011). Moreover, previous studies reported that college students' self-efficacy for condom use was a strong predictive factor for the intent to use condoms (Lee, 2010;Xiao, 2012). However, even after intervention, participants' confidence about communication with their partners about safer sex and condom negotiation strategies (e.g., refusal of sex without a condom) in this study was relative lower than other abilities to successfully practice cervical cancer prevention behaviors.…”
Section: Discussionsupporting
confidence: 90%
“…Some researchers found that partner sexual communications were also associated with condom use among various Chinese populations. For example, Xiao (2012) found that partner communication about condom use was the strongest predictor of condom use among Chinese college students sample, followed by condom use self-efficacy, subjective norms regarding condom use and positive health/relational attitudes. Another study explored the characteristics of sexual communications such as the topics of communication (e.g., condom use, HIV prevention, STDs prevention, sexual history, other sexual partnership) and target of communication (stable partners or casual partners) and their associations with condom use among a sample of MSM in Beijing (Xiao, Li, Liu, Li, & Jiang, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Despite these challenges, a large number of college students (74–82%) in China have not had sexual intercourse (Tang et al. ; Xiao ; Zhou et al. ).…”
Section: Introductionmentioning
confidence: 99%